Sequential drawings the New Yorker series - McGuire, Richard 1957- (Pantheon Books, 2016)
"Sequential Drawings gathers together more than a decade of McGuire's witty and endlessly inventive spots--a veritable short story collection--each drawing given its own spread, which, in turn, assures for the reader the experience of surprise and delight that the drawings unfailingly deliver. Richard McGuire's first series of "spot" drawings debuted in the New Yorker in February 2005 for the magazine's 80th anniversary issue. Spot drawings, scattered among the magazine's text, had been a long-running feature of The New Yorker, and over the years, many artists had contributed them. But McGuire was the first to conceive them as a sequence, and his drawings were something altogether new: deceptively simple images that imbued the series with movement and narrative, telling their own unexpected stories"--
Keywords: Zeichnung; Kunst; McGuire, Richard; Bildband